TUMOR-INFILTRATING LYMPHOCYTES IN TRIPLE NEGATIVE BREAST CANCER: CORRELATIVE ANALYSES OF OWN DATA AND LITERATURE REVIEW - Zakhartseva , Liubov; Yanovytska , Mariia (The Ukrainian Scientific Medical Youth Journal, 2019)
The article summarizes data and presents own study about the value of tumor-infiltrating lymphocytes as a prognostic factor for breast cancer including triple negative breast cancer lacking estrogen and progesterone receptors and HER2 ew amplification. This tumor group is heterogeneous and has lower overall and disease-free survival rates; therapeutic options for this tumor group are limited compared to luminal and HER2-positive tumors. Triple negative breast tumors attract the attention of scientists as they require more individualized approach and additional prognostic factors in the treatment. The aim of this study is to conduct correlation analysis of tumor-infiltrating lymphocytes with survival rates, stage of disease and degree of differentiation of triple negative breast tumors. Also determination of the most "immunogenic" histological subgroups of triple negative breast cancer is done, as well as comparing of tumor-infiltrating lymphocytes measurement as a continuous number and divided into groups. Samples (n = 143) from patients with triple negative breast cancer undergoing treatment at the Kyiv City Clinical Oncology Center during 2010-2015 were used. The assessment of the number of tumor-infiltrating lymphocytes was performed on histological glasses retrospectively, following the recommendations of an international group for the determination of immune-oncological biomarkers. The number of tumor-infiltrating lymphocytes was evaluated as a continuous number and also divided into groups A (0-10%), B (10-40%) and C (40-90%). According to the results of the study, there was a high direct correlation between the continuous number of tumor-infiltrating lymphocytes and divided into groups (A, B, C). A weak direct correlation was found between tumor-infiltrating lymphocytes and tumor differentiation rates, a weak inverse correlation between tumor-infiltrating lymphocytes count and overall survival and stage of disease, in particular tumor size. The rate of tumor-infiltrating lymphocytes for all carcinomas with medullary characteristics was 100%, indicating a high "immunogenicity" of this histological subtype of tumors. The study confirms that tumor-infiltrating lymphocytes act as an additional prognostic marker for malignant breast tumors, in particular, triple negative breast cancer. Determination of tumor-infiltrating lymphocytes is advisable in the routine practice of the pathologist who investigates malignant breast tumors since it requires no additional reactions and is economically viable. It is advisable to use the recommendations of an international group of the determination of immuno-cancer biomarkers for the distribution of this indicator by groups A, B, C for convenience of description.